Variation in the intensity and prevalence of macroparasites in migratory caribou : a quasi-circumpolar study - Simard, Alice-Anne; Kutz, Susan; Ducrocq, Julie; Brodeur, Vincent; Côté, Steeve D.; Beckmen, Kimberlee; Taillon, Joëlle; Campbell, Mitch; Croft, Bruno; Cuyler, Christine; Davison, Tracy; Elkin, Brett; et al. (Canadian Journal of Zoology, 2017)
Comparative studies across time and geographical regions are useful to improve our understanding of the health of wildlife populations. Our goal was to study parasitism in migratory caribou (Rangifer tarandus (L., 1758)) of North America and Greenland. A total of 1507 caribou were sampled across 12 herds to assess seven of their main helminth and arthropod macroparasites between 1978 and 2010. We sought to determine which factors such as sex, age class, herd size, and season best explained the prevalence and intensity of those parasites. Intensity of warble fly (Hypoderma tarandi (L., 1758)) larvae increased with age for males, whereas the opposite was observed in females. Prevalence of giant liver flukes (Fascioloides magna (Bassi, 1875) Ward, 1917), tapeworm Taenia hydatigena Pallas, 1766, and nose bot fly (Cephenemyia trompe (Modeer, 1786)) larvae was higher in adults than in calves. Prevalence of F. magna and T. hydatigena was higher at high herd size than at lower herd size. Greenland herds had the lowest prevalence of T. hydatigena and of the tapeworm Taenia krabbei Moniez, 1879, a higher intensity of H. tarandi, and a higher prevalence of C. trompe than the other herds. Of the herds from Quebec and Labrador, the Rivière-George herd had a higher prevalence of F. magna than the Rivière-aux-Feuilles herd. Our research provides the first comparative survey of these parasites of caribou across a broad spatial–temporal range. Les études comparatives réalisées avec un large éventail spatio-temporel sont fort utiles pour améliorer notre compréhension de l’état de santé des populations d’animaux sauvages. Nous avons étudié le parasitisme chez le caribou migrateur (Rangifer tarandus (L., 1758)) en Amérique du Nord et au Groenland. Un total de 1507 caribous ont été échantillonnés à travers douze troupeaux pour sept de leurs principaux helminthes et arthropodes macroparasites entre 1978 et 2010. Nous avons tenté de déterminer quels facteurs tels que le sexe, la classe d’âge, la taille du troupeau et la saison ...